Shotgun Environmental DNA, Pollen, and Macrofossil Analysis of Lateglacial Lake Sediments From Southern Sweden - Parducci, Laura; Alsos, Inger Greve; Unneberg, Per; Pedersen, Mikkel W.; Han, Lu; Lammers, Youri; Salonen, J. Sakari; Väliranta, Minna M.; Slotte, Tanja; Wohlfarth, Barbara (Frontiers in Ecology and Evolution, 2019)
The lake sediments of Hässeldala Port in south-east Sweden provide an archive of local and regional environmental conditions ~14.5-9.5 ka BP (thousand years before present) and allow testing DNA sequencing techniques to reconstruct past vegetation changes. We combined shotgun sequencing with plant micro- and macrofossil analyses to investigate sediments dating to the Allerød (14.1-12.7 ka BP), Younger Dryas (12.7-11.7 ka BP) and Preboreal (<11.7 ka BP). Number of reads and taxa were not associated with sample age or organic content. This suggests that, beyond the initial rapid degradation, DNA is well preserved. The proportion of recovered plant DNA was low, but allowed identifying an important number of plant taxa, thus adding valid information on the composition of the local vegetation. Importantly, DNA provides a stronger signal of plant community changes than plant micro- and plant macrofossil analyses alone, since a larger number of new taxa were recorded in Younger Dryas samples. A comparison between the three proxies highlights differences and similarities and supports earlier findings that plants growing close to or within a lake are recorded by DNA. Plant macrofossil remains moreover show that tree birch was present close to the ancient lake since Allerød; together with the DNA results, this indicates that boreal to subarctic climatic conditions also prevailed during the cold Younger Dryas interval. Increasing DNA reference libraries and enrichment strategies prior to sequencing are necessary to improve the potential and accuracy of plant identification using the metagenomic approach.